AL-SAMÂ’ WA AL-QIYÂS FÎ HAML AL-LAFZH MA’NÂ ÂKHAR - Mohamed, Yuslina; Hajib, Zainal Abidin; Ahmad, Wan Azura Wan; Ibrahim, Mikail (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2017)
This study aimed to clarify the two criteria: hearing and the measurement in the images of inclusion in verbs, nouns and letters. It discussed the views of scientists around them because of its moral and synthetic effects, and the inclusion images contained in the Koran. The study adopted the analytical method, comparing to the views of scientists on the subject in the books of language, interpretations, grammar and rhetoric for the preference of a strong over the weak. The result showed that the rule of Standard inclusion was unanimous in verbs, measurement is permissible on the names and characters for the prevalence of use.